Efektivitas Pemberian Jahe Merah (Zingiber Officinale Var Rubrum Rhizoma) Dan Teh Rosella (Hibiscus Sabdariffa) Terhadap Kegawatan Dismenore - Puji Setya Rini, Puji Setya Rini; Diah Agustina; Tiwi Pramesti (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Teenagers start to experience menstruation is one form of adolescence with biological development. Abdominal pain which is often called dysmenorrhea pain is often experienced by teenagers who are menstruating. The use of red ginger and rosella tea is one form of non-pharmacological treatment to reduce dysmenorrhea pain. The purpose of this study was to determine the effectiveness of red ginger and rosella tea in reducing dysmenorrhea in adolescent girls. The research method used a Quasy Experiment with a nonrandomized pretest - posttest approach, in this study design using 3 (three) groups, namely the group with the treatment of red ginger decoction, the group with the treatment of rosella tea and the control group. The sample in this study was the red ginger intervention group, the rosella tea intervention group and the control group with 30 respondents each. The results of the study were obtained using the Mann Whitney alternative test, a p value of 0.000 was obtained, meaning that statistically red ginger provided effectiveness on the dysmenorrhea pain scale in the intervention group. The conclusion statistically red ginger provided significant effectiveness on the pain scale in the intervention group with a p value of 0.000 (<0.05).